1995
DOI: 10.1021/ja00121a027
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Isomerism Based on Metal-Metal Bonds

Abstract: The stereodynamics of metal-metal bonds has remained virtually unexplored until very recently. It is now known that the barriers for the degenerate reorientation of metal-metal bonds can be substantial.1•1 2 This opens the way for the preparation of clusters which differ on the basis of their metalmetal bonding networks. A test of this idea entails demonstration that clusters can exist as geometric isomers based exclusively on the relative positions of -M bonds. This type of process assumes added significance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…This was first achieved by grafting on to the same [Ru 4 E 4 ] 2+ core different types of cyclopentadienyl ligands, namely C 5 H 5 , and C 5 Me 5 (Cp*). 28 Only one type of crystal structure was characterized, and the [(Cp) 2 (Cp*) 2 Ru 4 E 4 ] 2+ cluster looks quite similar to the parent compound with four identical Cp ligands: a distorted cubane with three bonding Ru-Ru contacts and three nonbonding Ru…Ru distances. However, the three metal-metal bonds are not distributed at random: the Cp*Ru centers each support two metal-metal bonds, suggesting that the corresponding metal atoms can be assigned as Ru IV (Scheme 9, form 4).…”
Section: 'Geometric Isomerism' In Cubane-like M 4 S 4 Clusters 2728mentioning
confidence: 99%
See 1 more Smart Citation
“…This was first achieved by grafting on to the same [Ru 4 E 4 ] 2+ core different types of cyclopentadienyl ligands, namely C 5 H 5 , and C 5 Me 5 (Cp*). 28 Only one type of crystal structure was characterized, and the [(Cp) 2 (Cp*) 2 Ru 4 E 4 ] 2+ cluster looks quite similar to the parent compound with four identical Cp ligands: a distorted cubane with three bonding Ru-Ru contacts and three nonbonding Ru…Ru distances. However, the three metal-metal bonds are not distributed at random: the Cp*Ru centers each support two metal-metal bonds, suggesting that the corresponding metal atoms can be assigned as Ru IV (Scheme 9, form 4).…”
Section: 'Geometric Isomerism' In Cubane-like M 4 S 4 Clusters 2728mentioning
confidence: 99%
“…At 290 °C, isomers 4 and 5 are present to the extent of 77 and 23%, respectively. 28 The metal-metal interactions in Cp…”
Section: 'Geometric Isomerism' In Cubane-like M 4 S 4 Clusters 2728mentioning
confidence: 99%
“…See http:// www.rsc.org/suppdata/dt/b3/b304119k/ can be distinguished by replacing for instance C 5 H 5 by C 5 Me 5 , real isomers based exclusively on the relative positions of the M-M bonds can be characterized from low-temperature NMR spectroscopy. 5 This form of isomerism, termed "geometric isomerism" by Rauchfuss et al, 5 is in fact relevant to the more general concept of "bond-stretch isomerism" defined by Stohrer and Hoffmann, 6 and later by Parkin, 7 in the sense that isomers retain the same atomic arrangement in the same molecular topography -the cubane cage -and differ only in the distance between the pairs of metal atoms displaying or not a localized bond. 8 Theoretical studies in polyoxometalate chemistry have also shown that the localization/delocalization duality of electron pairs in reduced polyoxoanions could lead to multiple energy minima and to bond-stretch isomerism.…”
Section: Introductionmentioning
confidence: 99%
“…This form of isomerism was investigated first by Rauchfuss et al in cubane-like Ru 4 E 4 Cp 4 clusters (E = S, Se, Te) oxidized into dicationic species. 4, 5 The neutral clusters can be viewed as nested dimers of Ru 2 E 2 Cp 2 butterfly moieties displaying each a single metal-metal bond and two bridging chalcogen atoms. A two-electron oxidation yields a mixed-valence Ru III /Ru IV cluster with a third, localized Ru-Ru bond.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, structural variability caused by deviation in bond length was found in the dinuclear ruthenium compound, [(Cp*RuCl) 2 (μ-Cl) 2 ] [ 10 , 11 ], in trinuclear cobalt [ 4 , 12 , 13 , 14 ] and chromium complexes [ 15 ]. Recently, two conformations of a dinuclear iron complex differing in valence angles and bond length were reported by Hammann et al [ 16 ].…”
Section: Introductionmentioning
confidence: 99%